5th International Electronic Conference on Sensors and Applications 2018
DOI: 10.3390/ecsa-5-05723
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Low-Cost Piezoelectric Sensor for Three Phase Induction Motor Load Estimation

Abstract: Due the complexity of control and automation networks in modern industries, sensor-based systems stand out as effective approaches for failure detection in electrical and mechanical machines. This kind of intervention has a high operational value in industrial scenarios, once it can avoid corrective maintenance stops, i.e., before the failure reaches a high level of severity and compromises the machine. Consequently, the development of sensors applied to non-destructive techniques (NDT) for failure monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The sensors used in this research were the piezoelectric diaphragms, which are similar to PZT ceramics. Also called buzzers, these components were generally applied as sound generators, however, many recent studies have used them as an AE sensor successfully [9,10]. These diaphragms have a circular brass plate with a diameter of 20 mm that houses a circular piezoelectric ceramic with a diameter of 14 mm, which is coated by a metallic film for electrical contact (Figure 1).…”
Section: Piezoelectric Sensorsmentioning
confidence: 99%
“…The sensors used in this research were the piezoelectric diaphragms, which are similar to PZT ceramics. Also called buzzers, these components were generally applied as sound generators, however, many recent studies have used them as an AE sensor successfully [9,10]. These diaphragms have a circular brass plate with a diameter of 20 mm that houses a circular piezoelectric ceramic with a diameter of 14 mm, which is coated by a metallic film for electrical contact (Figure 1).…”
Section: Piezoelectric Sensorsmentioning
confidence: 99%
“…The root mean square (RMS) technique is a method that has been proven successful when applied for vibration analysis. Previous work has shown that this technique is effective not only in characterization and diagnosis, but also in monitoring and estimating indicators of TIM faults [13]. Furthermore, the Equation:…”
Section: Rms Measurementioning
confidence: 99%
“…is described for discrete sampling, with n being the number of samples collected, and n v the value for the nth sample of the signal [13].…”
Section: Rms Measurementioning
confidence: 99%
“…Thus, vibration monitoring has already been proposed for bearing, rotor, stator, and gear or axis fault diagnosis, mostly for induction motors and wind turbines [3][4][5][6][7][8][9][10]. Additional applications of piezoelectric sensors are recently reported in [11,12] for load estimation and undervoltage detection also in induction motor drives. Relative research has also been conducted for fault diagnosis of other electrical motor types, such as permanent magnet DC motors [13], while stator fault monitoring of brushless DC (BLDC) motors is presented in [14,15].…”
Section: Introductionmentioning
confidence: 99%